Order statistics in control charts construction - Pekasiewicz, Dorota Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Order statistics are applied in construction of control charts that are used in statistical process control. Control charts monitor the average process level, volatility or extreme values: maximum and minimum. In the paper selected control charts are presented. They were used to analyze the quality of component of a home appliance which are produced by a home appliance manufacturer.